Analysis on premature cracking causes of ASTM A213-T12 superheater tube - Chen, Jianguo; Dong, Ji; Zhang, Hanwen; Huang, Yaxin; Ma, Qingjun; Wei, Yushun; Ma, Hengsheng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
The failure behavior of superheater tube prepared by ASTM A213-T12 steel was studied. The microstructure and hardness at different positions of the tube, and the element distribution at the crack position, as well as the morphology and phase composition of the corrosion layer were analyzed using optical microscopy (OM), microhardness tester, scanning electron microscopy (SEM), and X-ray diffractometer (XRD). The results indicate that the pearlite at the failure position undergoes spheroidization and the hardness is significantly reduced compared to the normal position. Failure is closely related to corrosion and creep. On the one hand, there is sulfur corrosion and oxidation corrosion on the outer layer of the superheater tube, which seriously reduces the thickness of the tube. On the other hand, the creep resistance of the tube is significantly reduced due to thinning. There are numerous creep voids in the microstructure at the failure site. Meanwhile, oxygen can diffuse into the voids to promote oxidation corrosion.